Dietary Probiotics or Synbiotics Supplementation During Gestation, Lactation, and Nursery Periods Modifies Colonic Microbiota, Antioxidant Capacity, and Immune Function in Weaned Piglets - Wang, Kai; Zhu, Qian; Kong, Xiangfeng; Song, Mingtong; Azad, Md. Abul Kalam; Xiong, Liang; Zheng, Yuzhong; He, Qinghua (Frontiers in Veterinary Science, 2020)
This study was conducted to investigate the effect of dietary probiotics or synbiotics supplementation on colonic microbiota, antioxidant capacity, and immune function in weaned piglets. A total of 64 pregnant Bama-mini sows and then 128 of their weaned piglets were randomly assigned into control group, antibiotics group, probiotics group, or synbiotics group. The results showed that colonic Firmicutes and Bifidobacterium abundances in the probiotics group and total bacteria, Bacteroidetes, and Lactobacillus abundances in the synbiotics group were increased (P < 0.05), while Escherichia coli abundance in the synbiotics group was decreased (P = 0.061) compared with the control group. Firmicutes, Bifidobacterium, and total bacteria abundances were increased (P < 0.05) in the probiotics and synbiotics groups compared with the antibiotics group. Probiotics supplementation up-regulated (P < 0.05) the mRNA expression of GPR109A compared with the control and antibiotics groups. Dietary probiotics or synbiotics supplementation improved the antioxidant capacity by increasing (P < 0.05) the colonic CAT, GSH-Px, SOD, and T-AOC levels and plasma CAT, GSH, GSH-Px, and SOD levels and by decreasing (P < 0.05) the colonic and plasma MDA and H2O2 levels. Compared to the control group, the colonic IL-10, IFN-α, and sIgA concentrations and plasma IgA, and IgM concentrations were significantly increased (P < 0.05) in the probiotics and synbiotics groups. Spearman’s correlation analysis showed that the changed colonic microbiota, such as Lactobacillus and Bifidobacterium were correlated with the alteration of antioxidant indexes, cytokines, and immunoglobulins. In conclusion, dietary probiotics or synbiotics supplementation during gestation, lactation, and nursery periods could be used as an alternative for antibiotics in terms of gut health of weaned piglets.